Recruitment of benthic invertebrates in high Arctic fjords: Relation to temperature, depth, and season. (30th May 2017) - Meyer, Kirstin S.; Sweetman, Andrew K.; Kuklinski, Piotr; Leopold, Peter; Vogedes, Daniel; Berge, Jørgen; Griffiths, Colin; Young, Craig M.; Renaud, Paul E.
Abstract: In the high Arctic, recruitment of hard‐bottom benthic organisms has been studied at single locations, but little is known about how it varies spatially or temporally, or how it is influenced by abiotic factors. In this study, settlement plates were simultaneously deployed at five locations in three Svalbard (Norway) fjords at depths ranging from 7 m to 215 m. Recruitment was significantly different among fjords and among locations within a fjord. Recruits at each site co‐occurred randomly even though interspecific overgrowth was observed. This finding provides further evidence that there is not necessarily a relationship between non‐random co‐occurrence and interspecific competition, such as is traditionally assumed for other isolated, island‐like habitats. We found significantly lower recruitment in an Arctic‐influenced fjord than in more Atlantic‐influenced fjords. The abundance and richness of recruits was significantly lower in fall‐winter than in spring‐summer, but the spirorbid Circeis armoricana recruited in high abundance in fall‐winter. Both the abundance and taxonomic richness of recruits declined exponentially with depth, with the hydroid Stegopoma plicatile dominating at 215 m in an Atlantic‐influenced fjord. The most abundant recruiting taxa ( C. armoricana, Semibalanus balanoides, Harmeria scutulata, Celleporella hyalina ) can be described as pioneer (early‐succession) species. Crustose coralline algae, a slow‐growing superior competitor, also recruited at one location. Recruitment in Svalbard is highly variable, both spatially and temporally, and our results show the influence of local factors such as adult species composition.